An Integrated Approach to Evaluation of Blasts - A Case Study - Chung S (The Australasian Institute of Mining and Metallurgy, 1990)
The problems associated with equating calculated and measured properties of explosives with blast results are examined. The results from six full-scale test blasts in a limestone quarry are described. The purpose of the full-scale trial was two-fold, i) assess the role of varying aluminum levels (10% maximum) in a given explosive in terms of blasting performance, and, ii) find correlation between calculated, as well as measured properties of explosives and the resulting blasting performance. Each blast consisted of 36 holes, initiated with short period detonators in a staggered 3-row 2.4 m x 2.7 m (burden x spacing) pattern. Each 75 mm diameter borehole with no subgrade contained on the average 22 kg of 65 mm diameter cartridged explosive. The bench height was 6.3 m, with an average collpr of 1.2 m. The calculated and mgasured properties of explosive included, strength, detonation and explosion pressure, VOD, plate-dent depth, underwater bubble and shock energy, and the total energy efficiency. Each blast was instrumented to measure detonation velocity, initiation sequence, muck pile motion by means of high-speed photography and blasting vibrations. The post-blast measurements included photogrammetric survey of muck pile for size distribution on surface, muck pile profile, as well as the extent of backbreak. The results showed that the overall blasting performance of the explosive in question was nearly commensurate with the level of aluminum in the explosive, and there was excellent correlation between the underwater test properties and the blast results. The study also exemplified the need for more extensive post-blast analysis than is usual practice, for quantitative assessment of blasting performance of explosives and providing the necessary data-base for calibration of blasting models.